RADIOLOGY REPORT: PAST, PRESENT AND FUTURE - V. E. Sinitsyn (Вестник рентгенологии и радиологии, 2016)
The analysis of literature data showed that the creation and implementation of a new form of radiology reports into clinical practice is an actual problem of modern medicine. Although imaging modalities have undergone dramatic evolution over the past century, radiology reporting has remained largely static, in both content and structure. In recent years the necessity to create a structured reporting is widely discussed in the literature. A universal format of radiology report hasn’t been found yet. The standard of reporting system is absent, a wide variety of styles in radiology reporting currently exists. The challenging goal is improvement of existing protocols and creation of a new form of radiology reports – the protocols of the future.